2020
DOI: 10.3390/biom10111517
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of All Human Sulfotransferases in Fission Yeast, Assay Development, and Structural Models for Isoforms SULT4A1 and SULT6B1

Abstract: Cytosolic sulfotransferases (SULTs) catalyze phase II (conjugation) reactions of drugs and endogenous compounds. A complete set of recombinant fission yeast strains each expressing one of the 14 human SULTs was generated, including SULT4A1 and SULT6B1. Sulfation of test substrates by whole-cell biotransformation was successfully demonstrated for all enzymes for which substrates were previously known. The results proved that the intracellular production of the cofactor 3′-phosphoadenosine 5′-phosphosulfate (PAP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Although, SULT4A1 contains the highly conserved SULT-catalytic Lys-Lys-His residues, no sulfation activity by SULT4A1 for small (physiological) compounds has been reported 1 , 3 , 4 , 25 . A recent report suggested that SULT4A1 is able to sulfonate 1-napthol using the S. pombe ‘enzyme’ bag assay, yet this observation has not been reproduced by other laboratories 32 . Fission yeast and budding yeast do not possess any endogenous SULT-activity.…”
Section: Discussionmentioning
confidence: 96%
“…Although, SULT4A1 contains the highly conserved SULT-catalytic Lys-Lys-His residues, no sulfation activity by SULT4A1 for small (physiological) compounds has been reported 1 , 3 , 4 , 25 . A recent report suggested that SULT4A1 is able to sulfonate 1-napthol using the S. pombe ‘enzyme’ bag assay, yet this observation has not been reproduced by other laboratories 32 . Fission yeast and budding yeast do not possess any endogenous SULT-activity.…”
Section: Discussionmentioning
confidence: 96%
“…The recombined fission yeast strains YN3, YN4, YN20, and YN25 used in this project were described before (Sun et al, 2020). The preparation of media and basic manipulation methods of S. pombe were carried out as described (Alfa et al, 1993).…”
Section: Fission Yeast Strains Media and General Techniquesmentioning
confidence: 99%
“…This was essentially done as described before (Sun et al, 2020) with slight modifications. Briefly, fission yeast strains were grown in 10 ml liquid culture of EMM at 30 °C and 230 rpm for 24 h. Incubation of main cultures in 250 ml Erlenmeyer flasks was performed subsequently.…”
Section: Biotransformation With Enzyme Bagsmentioning
confidence: 99%
See 2 more Smart Citations